Features of development of organizations in the context of digital transformation - Yu. V. Vertakova; O. A. Kryzhanovskaya (Вестник университета)
The article characterizes the main trends in the development of organizations in modern economic conditions: the spread of coronavirus infection, a new industrial revolution, a shift in political courses, an increase in economic nationalism, a desire to maintain sustainability, digital transformation. To achieve the goal - to identify the features of the development of organizations in the context of digital transformation - the authors investigated the status of digital transformation in the Russian Federation by industry, the priorities of the digital transformation directions of Russian companies, the success factors of digital transformation. The paper analyses the use and implementation of modern technological solutions in the activities of enterprises in the context of digital transformation. In conclusion, the authors emphasize the role of the head of an organization that implements digital technologies to achieve strategic goals in the context of the transformation of the economic space.